Fast geomagnetic field intensity variations between 1400 and 400 BCE: new archaeointensity data from Germany - Hervé, Gwenaël; Wittenborn, Malte Fabian (Physics of the earth and planetary interiors, 2017)
Thirty-five mean archaeointensity data were obtained on ceramic sherds dated between 1400 and 400 BCE from sites located near Munich, Germany. The 453 sherds were collected from 52 graves, pits and wells dated by archaeological correlation, radiocarbon and/or dendrochronology. Rock magnetic analyses indicate that the remanent magnetization was mainly carried by magnetite. Data from Thellier-Thellier experiments were corrected for anisotropy and cooling rate effects. Triaxe and multispecimen (MSP-DSC) protocols were also measured on a subset of specimens. Around 60% of the samples provide reliable results when using stringent criteria selection. The 35 average archaeointensity values based on 154 pots are consistent with previous data and triple the Western Europe database between 1400 and 400 BCE. A secular variation curve for central-western Europe, built using a Bayesian approach, shows a double oscillation in geomagnetic field strength with intensity maxima of ∼70µT around 1000-900 BCE and another up to ∼90µT around 600-500 BCE. The maximum rate of variation was ∼0.25µT/yr circa 700 BCE. The secular variation trend in Western Europe is similar to that observed in the Middle East and the Caucasus except that we find no evidence for hyper-rapid field variations (i.e. geomagnetic spikes). Virtual Axial Dipole Moments from Western Europe, the Middle East and central Asia differ by more than 2·1022A·m2 prior to 600 BCE, which signifies a departure from an axial dipole field especially between 1000 and 600 BCE. Our observations suggest that the regional Levantine Iron Age anomaly has been accompanied by an increase of the axial dipole moment together with a tilt of the dipole.